Effect of Environmental Intervention on the Consumption of Rice without Toxic Metals Based on the Health Belief Model and Ecological-Social Model - Shafiei, Leili (J Clin Diagn Res, 2017)
INTRODUCTION: The effect of instructional models on the changing behaviour of consuming contaminated rice with toxic metals has not been investigated in Iran yet. AIM: To compare effect of Health Belief Model (HBM) and Ecological (ECO) social model on decreasing the consumption of rice contaminated with toxic metals. MATERIALS AND METHODS: The study aimed at implementing a six-month interventionist program among three groups (HBM, ECO and Control). The study population comprised of 240 women, aged 18 to 50. Questionnaires were distributed which consisted of demographic information, knowledge, constructs of the models, performance of rice consumption, and the manner of rice cooking. In HBM group participants were individually provided with instructions based on HBM. However, in ECO group participants received the instruction through social networks consisted of mothers, sisters, family members, and colleagues. RESULTS: The results of Wilcoxon test indicated improvements in people’s diet including a significant increase in the number of women consuming rice without toxic metals, a significant reduction in the number of women consuming rice contaminated with toxic metals in both intervention groups. On the other hand, such an improvement was not observed in the control group. The results of repeated measures’ analysis of variance suggested further improvement in healthy diet in ECO group rather than HBM group after the completion of the environmental intervention. CONCLUSION: Both methods of instructional intervention caused changes in the diet of people regarding the consumption of rice free from toxic metals and changes in the manner of cooking from Kateh (steaming rice) to Pilaw (draining rice). Development of social support had probably a more effective role on the improvement of people’s diet.